INFLUENCE OF PROCESSING METHODS ON THE PHYTOCHEMICAL, MINERAL AND FIBRE FRACTION OF JUJUBE FRUIT MEAL AS A POTENTIAL FISH FEED INGREDIENT - Yakubu, Hadiza B.; Bichi, Armayau H.; Dauda, Akeem B. (FUDMA JOURNAL OF SCIENCES, 2025)
Most of the ingredients used in fish feed preparation are extremely competitive since they are eaten by man and utilized in agro allied industry, hence costly. Consequently, effort concerning using plant materials that are not used by man received less attention. Ziziphus mauritiana is a common fruit that is found widely in numerous regions of the world. Hence this study examined some nutritional characteristics of raw and differently processed Z. mauritiana fruit meal as a potential ingredient in fish feed preparation. The fruit meal was processed by boiling, toasting, soaking and fermenting using standard methods. The processed meals were examined in triplicates for phytochemicals, minerals and fibre fractions. The results revealed that alkaloid was reduced significantly in boiling by 66.22% while toasting reduced the tannin level significantly (P<0.05) compared to fermenting. Flavonoid was increased significantly in boiling and fermenting. Toasting also showed superior performance in mineral content by significantly (P<0.05) reduced sodium and increased calcium, magnesium, potassium and iron. The fibre fractions were also varied among the processing methods. The highest Ndf (41.43±0.89%) was observed in toasting, so also the highest Ivomd (71.55±0.09%) and they were different significantly from other treatments. The least Adl (lignin) was also recorded in toasting (2.41±0.33%) and it was different significantly from all other treatments. The study established that all the processing methods influenced the Jujube fruit meal, however, toasting conferred the highest positivity. A feeding trial with inclusion of the processed Jujube fruit meal is therefore recommended.